PASAR TRADISIONAL DAN MOBILITAS PEDAGANG DI WILAYAH GUNUNGKIDUL (KAJIAN AWAI ETNOARKEOLOGI) - Hari Lelono (BRIN, 1999)
The study of traditional markets has not been widely carried out by archaeological researchers, perhaps because of a lack of interest in undertaking such studies. In fact, if we look closely at the traditional markets that are scattered in the cities / villages of Java, they contain social, economic, cultural and technological phenomena that reflect a tradition that has existed since classical times, namely the influence of the Hindhu and Buddha culture in Java / Bali. To be able to get an overview of the market in the past, it can be done through two data, namely material culture and information from the past (ethnographic) and analogy with traditional markets that still exist.